PENGARUH PENERAPAN METODE MATERIAL REQUIREMENT PLANNING (MRP) DAN METODE ECONOMIC ORDER QUANTITY (EOQ) TERHADAP EFISIENSI BIAYA BAHAN BAKU - Maesaroh Maesaroh; Dina Yulia (The Asia Pacific Journal Of Management Studies, 2022)
The production process is an activity that is very important for the survival of the company. Every company, whether a manufacturing company or a service company, must have the same goal, which is to earn a profit, so as to obtain cost efficiency for the supply of plastic raw materials, where the inventory planning is formed, it expects to produce an efficient procurement of raw material costs, meeting consumer demand without going out of stock to the customer. raw materials, by applying appropriate methods in its production. One of them is through effective production and inventory management, namely through the Economic Order Quantity (EOQ) method and the Requirement Planning (MRP) method. The research method used is descriptive quantitative method, quantitative research is a research method based on the philosophy of positivism, used to examine certain populations or samples, data collection using research instruments, data analysis is quantitative/statistical. Descriptive analysis is an activity of inferring raw data in large quantities so that the results can be interpreted. Data collection techniques through interviews and documentation. The results show that the application of the Material Requirement Planning (MRP) method is more influential than the EOQ (Economic Order Quantity) method on the efficiency of raw material costs at PT Polytech Indo Hausen Tanggerang by determining the most economical totality of raw material costs without reducing the quantity in the production process.